Understanding primary care diagnosis and management of sleep disturbance for people with dementia or mild cognitive impairment: a realist review protocol - Greene, L; Aryankhesal, A; Megson, M; Blake, J; Wong, G; Briscoe, S; Hilton, A; Killett, A; Reeve, J; Allan, L; Ballard, C; Broomfield, N; et al. (BMJ Publishing Group, 2022)
Introduction The increasingly ageing population is associated with greater numbers of people living with dementia (PLwD) and mild cognitive impairment (MCI). There are an estimated 55 million PLwD and approximately 6% of people over 60 years of age are living with MCI, with the figure rising to 25% for those aged between 80 and 84 years. Sleep disturbances are common for this population, but there is currently no standardised approach within UK primary care to manage this. Coined as a ‘wicked design problem’, sleep disturbances in this population are complex, with interventions supporting best management in context.